Representatives of educational actors of physical education in primary schools and its relationship to educational reform in Algeria - mehdid, kahina; belmokhtar, Mohamed Redha; Brahimi, oum alsaadoud (sports creativity, 2025)
The Ministry of Education has decided from physical education one of its priorities as it has been included in school activities, so physical education is considered a mandatory subject that enters the curricula for each stage of education where boys and girls attend classes together in sports, but it is noticeable that the representations of the educational actors of this article are different with the prisms that It was required by the majority of actors neglecting this subject and replacing it with other school subjects So this study came to determine the importance of physical education, and to know the reality of practicing this subject in primary school